Amentoflavone Exerts Anti-Neuroinflammatory Effects by Inhibiting TLR4/MyD88/NF-κB and Activating Nrf2/HO-1 Pathway in Lipopolysaccharide-Induced BV2 Microglia - Shikuo Rong; Chunrong Yang; Feng Wang; Yiyang Wu; Kuishen Sun; Tao Sun; Zeyu Wu (Hindawi Limited, 2022)
Background. Amentoflavone, a natural biflavone, exerts anti-inflammation, antioxidation, and antiapoptosis effects on many diseases. However, the mechanism of amentoflavone on neuroinflammation-related diseases has not been comprehensively examined clearly. Methods. BV2 microglial cells were treated with amentoflavone (10 μM), followed by lipopolysaccharide (LPS). Microglial activation and migration ability and the expression of proinflammatory cytokines and other signaling proteins were determined using immunohistochemistry, immunofluorescence, quantitative real-time polymerase chain reaction, Western blotting, enzyme-linked immunosorbent assay, and wound-healing assays. Results. Amentoflavone restored LPS-induced microglia activation, migration, and inflammation response which depends on regulating toll-like receptor 4 (TLR4)/myeloid differentiation factor 88 (MyD88)/nuclear factor kappa B (NF-κB) pathway. In addition, amentoflavone also enhanced nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) levels in LPS-treated BV2 microglial cells. Conclusions. Amentoflavone ameliorated LPS-induced neuroinflammatory response and oxidative stress in BV2 microglia. These data provide new insight into the mechanism of amentoflavone in the treatment of neuroinflammation-related diseases. Therefore, amentoflavone may be a potential therapeutic option for neurological disorders.